Information Support for Women Entrepreneurs: a Study of Literature Review - Janet Jyothi, I. D.; Tadasad, P. G. (Journal of Information and Knowledge, 2014)
This article is a review of literature in the areas of women entrepreneurship, application of Information Communication Technology for providing information support. It highlights the efforts made by the government, non government organizations towards bridging the digital divide among women entrepreneurs in Karnataka.